2021
DOI: 10.2524/jtappij.75.373
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soluble Anthraquinone Application on Prehydrolysis Soda Cooking of Acacia crassicarpa Wood

Abstract: Acacia crassicarpa has a potential source as a renewable forest material in Indonesia. This research clarified the conditions to produce dissolving pulp with suitable properties from A. crassicarpa wood by prehydrolysis at 150℃ for 3 h and soda cooking at 160℃ for 3 h with application of 0.1% soluble anthraquinone (SAQ: 1,4-dihydro-9,10-dihydroxyanthracene sodium salt) . The presence of SAQ in soda cooking exhibited a significant increase in pulp yield (1.8%) compared to kraft cooking at a given kappa number (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Compared with the reported contents of lignin and acetone extracts of Acacia crassicarpa wood (31.5% and 2.08%, respectively) [ 16 ], these were low, and nitrobenzene oxidation of E. globulus wood resulted in a syringaldehyde (S)/vanillin (V) ratio of 4.60 and 2.22 mmol/g of lignin for S and V yields, respectively, indicating that the lignin had a more syringyl and non-condensed structure. The ratio of xylan to glucan in E. globulus (0.321) was higher than that of A. crassicarpa (0.265), which is advantageous for producing kraft pulp for paper materials.…”
Section: Resultsmentioning
confidence: 65%
“…Compared with the reported contents of lignin and acetone extracts of Acacia crassicarpa wood (31.5% and 2.08%, respectively) [ 16 ], these were low, and nitrobenzene oxidation of E. globulus wood resulted in a syringaldehyde (S)/vanillin (V) ratio of 4.60 and 2.22 mmol/g of lignin for S and V yields, respectively, indicating that the lignin had a more syringyl and non-condensed structure. The ratio of xylan to glucan in E. globulus (0.321) was higher than that of A. crassicarpa (0.265), which is advantageous for producing kraft pulp for paper materials.…”
Section: Resultsmentioning
confidence: 65%
“…Compared to kraft cooking (●) with the same AA dosage, the kappa number was lower by approximately nine points, but high yields of 40.5–40.9% were obtained, which was approximately four points higher than the soda-SAQ cooking, namely 36.5–37.2% ( p < 0.05). Utami et al [ 29 ] also reported high kappa numbers for the prehydrolysis kraft compared to the prehydrolysis soda-SAQ cooking of A. crassicarpa at an AA dosage of 17–20%.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies also reported the benefits of AQ addition in pulping, namely a lower kappa number and improved pulp yield for kraft/soda cooking of hardwood and non-wood materials [ 25 , 26 , 27 , 28 ]. Utami et al [ 29 ] revealed the advantages of prehydrolysis followed by soda with soluble anthraquinone (soda-SAQ) cooking over kraft cooking for Acacia crassicarpa , namely a higher pulp yield of 1.8% and a higher brightness level by 3.8–3.9 points. Jahan et al [ 30 ] also stated that the method led to additional decreases of 1.2–6.3 points in the kappa numbers of Acacia auriculiformis compared to the kraft and soda processes after bleaching.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Sansevieria, belonging to the family Agavaceae, is one of the ornamental plants [26]. Its unique and beautiful appearance has many benefits, including as a textile fiber, absorbing toxins, odors, and CO2 [19], even in an article mentioning that Sansevieria leaf extract can inhibit the growth of cancer cells [17].…”
Section: Resultsmentioning
confidence: 99%
“…Prehydrolysis soda-AQ pulp (10 g, as oven-dried weight) was oxygen (O) bleached at a PC of 30% for the oxygenperoxymonosulfuric acid-extraction with peroxideperoxymonosulfuric acid-extraction (O-Psa-Ep-Psa-E) TCF sequence. According to the previous procedure [17], peroxymonosulfuric acid (Psa) was synthesized by dropping 95% sulfuric acid (Wako Pure Chemical Industries, Ltd.) into a 45% hydrogen peroxide aqueous solution (Mitsubishi Gas Chemical Company, Inc.) at 70 o C. A target amount of Psa and a small amount of NaOH aqueous solution for adjusting to pH 3.0 were added to the pulp suspension at a PC of 10% in a polyethylene bag.…”
Section: Bleaching Sequences and Conditionsmentioning
confidence: 99%